COVID-19 vaccine hesitancy among Nigerians living with non-communicable diseases: a qualitative study - Ferdinand C Mukumbang; Lucia Y Ojewale (BMJ Open)
Objectives The discovery and subsequent manufacture of various types of COVID-19 vaccines were considered a breakthrough in the fight against the COVID-19 pandemic. Initially, limited supplies of COVID-19 vaccines warranted vulnerable populations such as people living with chronic non-communicable diseases and the elderly to be prioritised for vaccination. Nevertheless, the uptake of the COVID-19 vaccines among these populations was suboptimal. In this study, we aimed to describe the drivers of COVID-19 vaccine hesitancy among people living with chronic non-communicable diseases in Ibadan, Nigeria.Method We applied qualitative methods to explore the feelings and thoughts of people living with chronic non-communicable diseases towards COVID-19 vaccines, at a tertiary hospital in Ibadan, Nigeria. Data were obtained from 25 people living with chronic conditions through in-depth interviews. We thematically analysed the transcripts inductively and deductively. Dedoose qualitative data management software was used to manage the data.Findings Emerging subthemes were grouped into two major themes: Hesitancy towards the COVID-19 vaccine related to biological concerns and those related to sociopolitical issues. Hesitancy towards the COVID-19 vaccine associated with biological factors included: (1) concerns over the COVID-19 vaccine worsening the underlying chronic condition; (2) fear of harmful physiological consequences; (3) concerns over insufficient testing of vaccine for safety and (4) perceived vaccine infectiveness. Sociopolitical factors were related to (1) misconceptions of vaccines as a treatment for those with COVID-19; (2) mistrust of manufacturers (‘the whites’); (3) mistrust of government and (4) COVID-19 misinformation.Conclusion Public health education on the nature and benefits of the COVID-19 vaccine is urgently needed among people living with chronic non-communicable diseases. These measures could improve COVID-19 vaccine uptake and healthcare usage in general. Paying attention to these factors could have implications for the management of the next global pandemic requiring mass vaccination.